Albumin-bound paclitaxel drives a cytotoxic CD8+ T cell enriched immune microenvironment in triple negative breast cancer - Luo, Daiqin; Jin, Xianhuai; Zhang, Shuai; Zeng, Xianlin; Zhang, Shuling; Li, Daohong; Xiong, Wei; Luo, Yan; Hu, Zuquan; Long, Jinhua; Zeng, Zhu (Frontiers in Immunology, 2026)
BackgroundTriple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer characterized by high metastatic potential and resistance to conventional therapies, representing a significant clinical challenge. Although nano albumin-bound paclitaxel (nab-PTX) has demonstrated generally good treatment effect, the mechanisms underlying its enhanced therapeutic performance, particularly its potential immunomodulatory effects, remain unclear.MethodsUsing both in vitro and in vivo TNBC models, we investigated the immunomodulatory effects of nab-PTX. Specifically, we evaluated its ability to induce immunogenic cell death (ICD), activate dendritic cells (DCs) via the cGAS-STING signaling pathway, and influence CD8+ T cell recruitment and infiltration within the tumor microenvironment.ResultsTreatment with nab-PTX induced ICD in TNBC cells was associated with enhanced activation of DCs through the cGAS-STING pathway. This activation was accompanied by improved antigen presentation and a significant increase in intratumoral CD8+ T cell infiltration. Collectively, these immune alterations suggest that nab-PTX contributes to a more immunologically active tumor microenvironment, characterized by heightened T cell mediated immune engagement.ConclusionOur study indicate that, beyond its direct cytotoxic effects, nab-PTX may exert anti-tumor activity in TNBC through modulation of the tumor immune microenvironment. By inducing ICD and promoting DCs activation, nab-PTX appears to support CD8+ T cell recruitment, thereby potentially enhancing immune mediated tumor regression. This immunologically supportive role of nab-PTX highlights its potential value in strategies aimed at improving the efficacy of chemotherapy based or immunotherapy combined treatments in TNBC.